The Relationship between Knowledge about HIV/AIDS and Adolescents' Free Sexual Behavior - Fathia Fahkri Inayati Said; Fenska Makualaina; Lisma Natalia Br Sembiring; Nasrianti Nasrianti; Yance Ronald Rainuny; Yestiani Norita Joni (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adolescence is a transitional period that is vulnerable to risky behavior, including promiscuous sex. Lack of knowledge about HIV/AIDS can increase the risk of unsafe sexual behavior, which can potentially lead to HIV/AIDS transmission in adolescents. This study aims to determine the relationship between knowledge about HIV/AIDS and promiscuous sexual behavior in adolescents. This study used a quantitative design with a cross-sectional approach. The sample consisted of 61 students majoring in Nursing Assistant at SMK YPKP, selected using an accidental sampling technique. The research instruments consisted of an HIV/AIDS knowledge questionnaire and a Guttman scale questionnaire on promiscuity behavior. Data were analyzed univariately and bivariately using the Chi-Square test. The results showed that most respondents had sufficient knowledge about HIV/AIDS (78.7%) and negative promiscuity behavior (54.1%). Statistical tests showed a significant relationship between knowledge about HIV/AIDS and promiscuity behavior in adolescents (p-value = 0.000). All respondents with good knowledge (21.3 %) had positive promiscuity behavior. There is a significant relationship between knowledge about HIV/AIDS and adolescent sexual behavior. Good knowledge plays a crucial role in developing positive and safe sexual behavior.